General questions of methods of teaching fractal geometry to university students in conditions of fundamentalization of education - V S Kornilov (RUDN Journal of Informatization in Education, 2013)
In article methodical aspects, components of fundamental training of students of physical and mathematical specialties of higher educational institutions of fractal geometry are discussed. The attention to use in the course of such training of means of informatization is paid.